Smart Growth : How to Grow Your People to Grow Your Company. - Johnson, Whitney. (Harvard Business Review Press, 2022)
Learn. Leap. Repeat. Growth is the goal. Helping people develop their potential--enabling them to articulate and become the self they want to be, are capable of being, and that best serves them and others in the short and long term--is what we as individuals and leaders strive toward. But how do we grow? It turns out it happens in a predictable way, which means we can understand where we are in our growth and chart a way forward. In this compact, complete guide, Whitney Johnson dives more deeply than ever into the S curve of growth and learning so that you can envision how growth happens and direct yourself and others in your organization to create a culture that fosters it. The growth and learning journey comes in three phases: the Launch Point, the Sweet Spot, and the High End, and within each phase, individuals play roles that keep us moving up the curve toward our goals. Compelling examples of successful people will show you when and why growth is slow, how to keep going, what to do when growth and learning are almost too fast to keep up with, and how to leap from one growth journey to another. As individuals grow, so do organizations and societies. Growth is learning put into action, ideally action that betters the world as we better ourselves and our small niches, both personal and professional, within it. Growth occurs when learning is internalized, when we try something new and invest the effort to move it from being something we do to something we are.